2006
DOI: 10.1002/eji.200636316
|View full text |Cite
|
Sign up to set email alerts
|

Three common alleles of KIR2DL4 (CD158d) encode constitutively expressed, inducible and secreted receptors in NK cells

Abstract: Genetic polymorphism of KIR2DL4 results in alleles with either 9 or 10 consecutive adenines in exon 6, which encodes the transmembrane domain. "10A" alleles encode a membrane-expressed receptor that is constitutively expressed on resting CD56bright NK cells and on CD56 dim cells after culture. However, in some individuals with the 10A allele, KIR2DL4 cannot be detected on their resting CD56 bright NK cells. "9A" alleles have been predicted to encode a secreted receptor due to the splicing out of the transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 28 publications
5
78
1
Order By: Relevance
“…The induction of KIR expression on NK cells is poorly described in literature. Certain allelic variants of KIR2DL4 have been shown to be induced on cultured NK cells, either as a full-length and detectable protein, or as a secreted receptor (45). A higher KIR3DS1 expression on NK cells has been observed in vivo in the context of HIV infection (34).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of KIR expression on NK cells is poorly described in literature. Certain allelic variants of KIR2DL4 have been shown to be induced on cultured NK cells, either as a full-length and detectable protein, or as a secreted receptor (45). A higher KIR3DS1 expression on NK cells has been observed in vivo in the context of HIV infection (34).…”
Section: Discussionmentioning
confidence: 99%
“…3). Even a single nucleotide mutation can dramatically change receptor expression,25, 31, 32, 33 ligand specificity34, 35, 36 or signalling strength. KIR gene copy number variation influences NK cell education, shaping the NK cell repertoire 37.…”
Section: Kir Geneticsmentioning
confidence: 99%
“…Freshly isolated NK cells, but not cultured NK cells, produce IFN-g in response to sHLA-G We have previously shown that plate-bound anti-KIR2DL4 mAb stimulates IFN-g production from 14-d IL-2-cultured NK cells from donors with at least one KIR2DL4 10A-A allele, which encodes a membrane-expressed receptor (10). In view of reports that soluble anti-KIR2DL4 stimulates IFN-g from freshly isolated NK cells, we tested the ability of three different soluble anti-KIR2DL4 mAbs to stimulate IFN-g in 14-d cultured NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additional Abs in the EasySep kit were CD20, CD14, HLA-DR, and CD123. Purified NK cells were incubated with freshly irradiated Daudi feeder cells and 200 IU/ml rIL-2 (T3267; Sigma, St. Louis, MO) as described previously (10).…”
Section: Acquisition and Culture Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation